Performance Analysis of International Steel Manufacturers: A Benchmark Study for Steel Supply Chains - Tsung-Hsien Yang; Hyun-cheol Paul Choi (International Journal of Supply Chain Management, 2013)
We present a benchmarking study on efficiencies or performance of various global manufacturers in the steel manufacturing supply chain using the analysis of DEA models. We select appropriate variables including costs of goods sold as an input variable for purchasing performance measure and net sales as an output for distribution performance measure to be used in our DEA analysis. Our analysis results from the selected five international steel manufacturers would help supply chain managers in steel manufacturing industry to evaluate and compare other large steel manufacturers for making possible strategic alliance decisions with publically available data.